COMMUNITY-BASED TOURISM MANAGEMENT PADA EVENT BUDAYA GEBYURAN BUSTAMAN: PENGUATAN KAPASITAS KOMUNITAS MELALUI PARTISIPASI MASYARAKAT DALAM PENGEMBANGAN DESTINASI BERKELANJUTAN - Zahrina Nabila Abidin (CV. Lafadz Jaya, 2026)
This study aims to analyze the implementation of Community-Based Tourism Management (CBTM) through community participation in the Gebyuran Bustaman Cultural Event, as well as its contribution to community capacity building and local development. Employing a qualitative case study design , data were collected through field observations, documentation, and in-depth interviews with event organizers, community leaders, MSMEs, and local residents selected via purposive sampling. Data were analyzed using an interactive model comprising data condensation, display, and verification. The results indicate that the event successfully implements CBT by positioning residents as primary actors across all management stages : bottom-up planning via community meetings , collaborative and non-hierarchical organizing , active execution as ritual performers and culinary vendors , and participatory evaluation. This active involvement functions as a learning-by-doing platform that significantly enhances community capacity by driving local leadership regeneration among the youth , improving organizational skills , and fostering multi-stakeholder collaboration. Consequently, the event generates a positive cycle of urban destination sustainability by balancing economic gains for MSMEs , strengthening social cohesion , and preserving cultural heritage. This study concludes that the Gebyuran Bustaman Cultural Event is an effective instrument for community empowerment , demonstrating that grass-roots independence paired with proportional government support is vital for sustainable urban tourism.